Deletion of P2X2 and P2X3 Receptor Subunits Does Not Alter Motility of the Mouse Colon - DeVries, Matthew; Vessalo, Megan; Galligan, James J. (Frontiers in Neuroscience, 2010)
Purinergic P2X receptors contribute to neurotransmission in the gut. P2X receptors are ligand-gated cation channels that mediate synaptic excitation in subsets of enteric neurons. The present study evaluated colonic motility in vitro and in vivo in wild type (WT) and P2X2 and P2X3 subunit knockout (KO) mice. The muscarinic receptor agonist, bethanechol (0.3-3 micromolar), caused similar contractions of the longitudinal muscle in colon segments from WT, P2X2 and P2X3 subunit KO mice. Nicotine (1-300 micromolar), acting at neuronal nicotinic receptors, caused similar longitudinal muscle relaxations in colonic segments from WT and P2X2 and P2X3 subunit KO mice. Nicotine-induced relaxations were inhibited by nitro-L-arginine (NLA, 100 micromolar) and apamin (0.1 micromolar) which block inhibitory neuromuscular transmission. ATP (1-1000 micromolar) caused contractions only in the presence of NLA and apamin. ATP-induced contractions were similar in colon segments from WT, P2X2 and P2X3 KO mice. The mouse colon generates spontaneous migrating motor complexes (MMCs) in vitro. The MMC frequency was higher in P2X2 KO compared to WT tissues; other parameters of the MMC were similar in colon segments from WT, P2X2 and P2X3 KO mice. 5-Hydroxytryptophan-induced fecal output was similar in WT, P2X2 and P2X3 KO mice. These data indicate that nicotinic receptors are located predominately on inhibitory motor neurons supplying the longitudinal muscle in the mouse colon. P2X2 or P2X3 subunit containing receptors are not localized to motorneurons supplying the longitudinal muscle. Synaptic transmission mediated by P2X2 or P2X3 subunit containing receptors is not required for propulsive motility in the mouse colon.